Determination of Current Flow Induced by Transcutaneous Electrical Nerve Stimulation for the Treatment of Migraine: Potential for Optimization - Thomas, Chris; Truong, Dennis Q.; Lee, Kiwon; Deblieck, Choi; Androulakis, Xiao Michelle; Datta, Abhishek (Frontiers in Pain Research, 2021)
Transcutaneous electrical nerve stimulation (TENS) for migraine involves the application of pulsatile stimulation through electrodes placed on the forehead to target the underlying trigeminal nerves. It is a simple, safe modality and has secured clinical approval in several markets including the European Union and United States. Despite nearing almost 7 years of use (post clinical approval), the exact mechanism of action is not fully known. Guided by the need to stimulate the trigeminal nerves bilaterally, electrode dimensions are simply required to extend enough to cover the underlying nerves. The goal of this study is to examine induced current flow (magnitude and spatial distribution of electric field) and another driver of stimulation (activating function) due to TENS therapy for migraine- for the first time. We further consider the effect of changing the electrode dimension and shape and propose a design modification to deliver optimal flow. Methods: We developed the first ultra-high-resolution finite element model of TENS for migraine incorporating the target supratrochlear (ST) and the supraorbital (SO) nerves. We first simulated the clinically approved V-shaped geometry. We then considered three additional designs: Extended V-shaped, idealized Pill-shaped, and finally an extended V-shaped but with greater contact spacing (Extended V-shaped +CS). Results: Our findings revealed that the clinically approved electrode design delivered substantially higher current flow to ST nerve in comparison to the SO nerves (Medial: 53% and Lateral: 194%). Consideration of an extended design (~10 mm longer and ~ 4 mm shorter) and a pill-like design had negligible impact on the induced current flow pattern. The Extended V-shaped+CS montage delivered relatively comparable current flow to each of the three target nerves. The electric field induced in the ST nerve was 49% and 141% higher in the Medial and Lateral SO nerve respectively. When considering maximum values, delivery of comparable stimulation was further apparent. Given the existing electrode design’s established efficacy, our results imply that preferential targeting of the ST nerve is related to mechanism of action. Additionally, if comparable targeting of all three nerves continues to hold promise, the Extended V-shaped +CS montage presents an optimized configuration to explore in clinical studies.